Removal of viruses from Lebanese fig varieties using tissue culture and thermotherapy - CHALAK, Lamis; ELBEAINO, Toufic; ELBITAR, Ahmad; FATTAL, Tala; CHOUEIRI, Elia (Phytopathologia Mediterranea, 2015)
Two Lebanese fig accessions of local varieties (Biadi and Aswad), infected by Fig leaf mottle-associated virus 1 (FLMaV-1), Fig leaf mottle-associated virus 2 (FLMaV-2) and Fig mosaic virus (FMV), were subjected to tissue culture and thermotherapy for producing virus-free plant material. The virus status of all progeny explants was assayed by RT-PCR using viruses-specific primers. The shoot tip culture technique was reliable for elimination of from 60 to 100% of fig viruses. However, stem cutting culture coupled with thermotherapy was the most effective for shoot regeneration (40% of reactive explants), while elimination of the three viruses was possible even though with lower rates of removal (from zero to 81%) were achieved. This study has indicated that FLMaV-2 is more susceptible to thermotherapy than FLMaV-1 and FMV.